Postcolonial linguistic voices : identity choices and representations - Anchimbe, Eric A.; Mforteh, Stephen A. (Contributions to the sociology of language ;, 2011)
This book studies discourses and linguistic choices in both ex-colonized and ex-colonizer communities as each copes with the outcomes of colonialism. The construction of identities, the translation of religious texts, the discursive construction of nations, the use of Indigenized varieties of colonial languages, and the emergence of diaspora communities are salient topics in postcolonial linguistics, and are treated here with great expertise by the authors. The book complements and expands upon traditional descriptions of multilingualism.